KEMAMPUAN PREDIKSI VARIABEL KONSERVATISMA AKUNTANSI DAN CORPORATE GOVERNANCE DALAM PENGUNGKAPAN KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI PT BURSA EFEK INDONESIA - Pradnyanitasari, Putu Dian; Sukartha, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
Financial statements are the basis of an assessment a company's financial performance, which in the financial statement as a whole the evidence shows and description of business management governance in managing the resources of the company. Previous studies often examine the relationship between financial ratios and financial performance. This study is a replication of the study Smith et al. (2011) in which the purpose of this research is to build a model that can predict the financial performance of the company by adding a variable conservatism and corporate governance for all listed companies in Indonesia Stock Exchange in 2011. The method of sample selection using purposive sampling to obtain 143 companies that were sampled, where the data were analyzed using factor analysis and discriminant analysis. The results showed that additional variables such as conservatism and corporate governance did not have a positive relationship with the company's financial performance and are not able to improve the accuracy of prediction models the company's financial performance.
Keywords: conservatism, corporate governance and corporate financial performance